Dynamics of enzymatic activity in primary culture of Syrian hamster adherent leukocytes ex vivo infected with SARS-CoV-2 - Svetlana A. Abramova; Irina N. Lyapun; Elena I. Drobot; Natalia V. Krylova; Olga V. Iunikhina; Valeria A. Lubova; Evgeniy K. Merlov; Iurii A. Belov; Larisa M. Somova; Mikhail Yu. Shchelkanov (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. The continued epidemic relevance of SARS-CoV-2, even after the end of the associated COVID-19 pandemic in 2023, necessitates further study of the interaction of this virus with the first line of cellular defense, neutrophils.